Novel Host Protein TBC1D16, a GTPase Activating Protein of Rab5C, Inhibits Prototype Foamy Virus Replication - Yan, Jun; Zheng, Yingcheng; Yuan, Peipei; Wang, Shanshan; Han, Song; Yin, Jun; Peng, Biwen; Li, Zhi; Sun, Yan; He, Xiaohua; Liu, Wanhong (Frontiers in Immunology, 2021)
Prototype foamy virus (PFV) is a member of the oldest family of retroviruses and maintains lifelong latent infection in the host. The lifelong latent infection of PFV may be maintained by the restriction factors of viral replication in the host. However, the mechanisms involved in PFV latent infection are poorly understood. Here, we found that TBC1D16, a TBC domain-containing protein, is significantly down-regulated after PFV infection. Tre2/Bub2/Cdc16 (TBC) domain-containing proteins function as Rab GTPase-activating proteins (GAPs) and are participates in the progression of some diseases and many signaling pathways. However, whether TBC proteins are involved in PFV replication has not been determined. Here, we found that TBC1D16 is a novel antiviral protein that targets Rab5C to suppress PFV replication. Overexpression TBC1D16 inhibited the transcription and expression of Tas and Gag, and silencing TBC1D16 enhanced the PFV replication. Moreover, the highly conserved amino acid residues R494 and Q531 in the TBC domain of TBC1D16 were essential for inhibiting PFV replication. We also found that TBC1D16 promoted the production of PFV-induced IFN- and the transcription of downstream genes. These results suggest that TBC1D16 might be the first identified TBC protein that inhibited PFV replication and the mechanism by which TBC1D16 inhibited PFV replication could provide new insights for PFV latency.